Reimplantation of a Large Extruded Segment of Tibia in an Open Fracture in a Pediatric Patient - Afshar, Ahmadreza; Tabrizi, Ali (The Surgery Journal, 2019)
A 6-year-old boy presented with a Gustilo type IIIB open fracture on his left leg with a segment of bone loss in his tibia. The boy's attendants brought two bone fragments recovered from the scene of the accident. The extruded bones were a segment with a length of 5.5 cm and a cortical bone with a length of 4 cm. The extruded fragments were reimplanted after scrubbing with 10% povidone–iodine for 20 minutes, soaking in 2% chlorhexidine solution for 20 minutes, and rinsing with normal saline. Four months after the injury, the extruded fragments were incorporated in the callus of the fracture site and complete fracture union in appropriate alignment was achieved.
Keywords: extruded bone; open fracture; reimplantation; tibia fracture; chlorhexidine gluconate; povidone–iodine